Admissibility of digital evidence in Indonesia: Criminal–civil implications for the chain of custody and evidentiary validity - Litya Surisdani Anggraeniko; Auliah Ambarwati; Feby Reski Utami (Priviet Social Sciences Journal, 2026)
Digital evidence has become a cornerstone of modern litigation in Indonesia; however, its admissibility remains complex because of the varying standards of proof across legal regimes. This study analyzes the construction of digital evidence admissibility following the enactment of Law No. 20 of 2025 (The New Criminal Procedure Code) and its harmonization with Law No. 11 of 2008 (UU ITE). Methodologically, this research employs a doctrinal legal analysis with a conceptual and statutory approach, utilizing court judgments as doctrinal illustrations to identify judicial inconsistencies in handling electronic data. The findings reveal that while Article 177 paragraph (1) letter f of Law No. 20/2025 now explicitly recognizes electronic information as independent evidence, its validity is strictly contingent upon Chain of Custody (CoC) compliance. In criminal proceedings, CoC lapses, such as failure in hashing or unauthorized access, frequently lead to the exclusion of evidence beyond a reasonable doubt. Conversely, in civil cases, procedural defects typically result in a reduction in probative value rather than total inadmissibility, governed by the principle of functional equivalence. To mitigate judicial disparity, this study proposes a Criminal–Civil Admissibility Matrix and a Minimum CoC Checklist comprising five technical indicators: lawful acquisition, hashing, forensic imaging, documented transfer, and expert certification. These frameworks serve as normative guides to ensure the integrity, authenticity, and reliability of digital proof in the Indonesian judiciary.